Memory functioning 7 years after severe childhood traumatic brain injury: Results of the Traumatisme Grave de l'Enfant study. Issue 1 (15th April 2021) - Câmara‐Costa, Hugo; Viot, Solène; Francillette, Leila; Opatowski, Marion; Toure, Hanna; Brugel, Dominique; Laurent‐Vannier, Anne; Meyer, Philippe; Watier, Laurence; Dellatolas, Georges; Chevignard, Mathilde
Abstract : Objective: To explore memory functioning 7 years after severe paediatric traumatic brain injury (TBI), associated factors, and relationships with other outcomes. Method: Children aged 0–15 years ( n  = 65), consecutively admitted over a 3‐year period in a single trauma centre, who survived after severe non‐inflicted TBI, were included in a prospective longitudinal study. Memory assessments were performed 7 years post‐injury using the Children's Memory Scale or the Wechsler Memory Scale (WMS IV), according to age. The General Memory Score (GMS‐7) was the primary outcome. Results: Thirty‐seven patients were available for assessment at 7 years post‐injury. Mean GMS‐7 was in the low average range ( M  = 84.9, SD  = 12.1). Lower GMS‐7 was significantly associated with markers of higher injury severity, such as length of coma. One year post‐injury functional and disability outcomes explained 74% of the variance of GMS‐7. Concurrent intellectual ability and type of ongoing education correlated strongly with GMS‐7. Age at injury and parental education were not associated with memory outcome. Conclusions: Memory functioning is variable but often strongly impaired several years after severe paediatric TBI, and is mostly related to injury severity, functional outcomes measured 1 year post‐injury, and concomitant cognitive and educational outcomes. GMS‐7 was lower at 7 years than one year post‐injury, supporting the importance of long term follow‐up.